The Field of Facemask Expressions Recognition Using PCA Classifier - Thakur, Gesu (Journal of Advanced Research in Signal Processing and Applications, 2023)
Many computer vision and machine vision researchers are working towards the direction of making HCI (Human-Computer Interface) systems, which can behave similarly to HHI (Human-Human Interface) systems. To make all these systems realistic the computer system has to understand the logic behind the power of humans to identify the emotions present on other’s faces during any kind of communication. The main challenges in the field of emotion detection are illumination conditions; pose variations, facial accessories, etc. In this paper, the main focus is on various steps which must be followed by the users to identify the emotion present on the face of the person whose image is under observation. The main emphasis is given to the sequence of steps followed to get the emotion from the face by using various concepts of image processing. These sequential steps are Face recognition to confirm that the image under consideration has a facial data or not, Detection of the face region from the image, Extraction of Region of Interest (ROI) from facial data, at the end the identification of the category of the emotion present on the detected face from the image supplied as input.